Determinants of formal financial services in the development of entrepreneurship in rural Ecuador - Guzmán Barquet, Eduardo Andrés (2023)
Purpose: To analyze the determinants of access to and use of formal financial services through the banking correspondent channel on the development of enterprises in rural areas of Ecuador. Method: Qualitative case study methodological strategy. Eighteen rural communities of the Coast and Highlands of Ecuador were studied. A thematic analysis was carried out to identify and analyze recurring patterns within the data. themes and sub-themes were categorized, allowing for the exploration of underlying meanings of interviews. Through an inductive analysis in Atlas.ti 9. The concepts identified in the interviews and the researcher's files were reviewed and the results were compared with the theoretical assumptions specified in the literature. Results: The main new contribution of this research to the business management knowledge of this research was the following: This study showed that there is a gap on the effect of banking correspondents without access to credit on the economic development of communities. In the case of Ecuador, correspondents differ in that they do not grant credit, which reaffirms that financial inclusion generates business development, not access to credit. The presence of the correspondent in communities has eliminated non-financial transaction costs by reducing the physical distance between the user and the distributor of financial services. The non-payment of non-financial transaction costs positively affected the generation of savings; in addition, the presence of the correspondent allowed the inhabitants to open savings accounts, which are used for personal and business transactions. Many businesses started their activities after the incorporation of the correspondent due to the concentration of potential customers of local businesses. In addition, the growth of business after correspondent banking is generated from the savings of time and money. 7 Limitations and recommendations for future research: It is recommended to empirically address the effect of access to financial services, without considering credit, on economic development and poverty reduction.